Uso de la WebQuest en el aprendizaje de funciones cuadráticas en décimo año, Unidad Educativa “Hualcopo Duchicela” - Quishpi Pilamunga, Ana Lucia (2024)
Globalization has caused significant changes in the world, especially in the educational field, as it promotes the renewal of traditional teaching methods with the help of various digital technical tools due to the needs of the environment. The present research aims to determine the impact of using WebQuest on the learning of quadratic functions in tenth-grade students at the "Hualcopo Duchicela" Educational Unit. It is done to promote understanding and motivation for the concept of Quadratic Functions. This study is characterized by being quasi-experimental design, explanatory in nature, and field study based. On the other hand, it is worth mentioning that the study involved a population of 72 tenth-grade students, from which a sample of 24 students from class "A" of the mathematics subject was selected. Finally, after the analysis and treatment of information through a comparison of means using a non-parametric Mann-Whitney U test, with a p-value of 0.0000056, it was determined that there are significant differences in the level of learning of quadratic functions in the experimental group of tenth-grade students at the "Hualcopo Duchicela" Educational Unit. Additionally, the survey applied to the experimental group showed that the majority of students exhibited a favorable attitude towards the application and use of WebQuest.